Beginning and intermediate algebra - R. David Gustafson (Thomson Brooks/Cole, 2008)
Get the grade you want in algebra with Gustafson and Frisk's BEGINNING AND INTERMEDIATE ALGEBRA! Written with you in mind, the authors provide clear, no-nonsense explanations that will help you learn difficult concepts with ease. Prepare for exams with numerous resources located online and throughout the text such as online tutoring, Chapter Summaries, Self-Checks, Getting Ready exercises, and Vocabulary and Concept problems. Use this text, and you'll learn solid mathematical skills that will help you both in future mathematical courses and in real life!